2015
DOI: 10.5505/tjtes.2015.28235
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of the neutrophil-to-lymphocyte ratio in patients with acute mesenteric ischemia: A retrospective cohort study

Abstract: BACKGROUND: Acute mesenteric ischemia (AMI) remains fatal in 50-70% of cases. AMI is recognized as a vascular emergency, requiring rapid and efficient clinical evaluation and treatment. In the present retrospective study, the possible utility of the neutrophillymphocyte ratio (NLR) in the early diagnosis of AMI was explored. The potential use of this ratio to distinguish AMI from non-vascular bowel necrosis (NVBN) was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 17 publications
(25 reference statements)
3
29
0
Order By: Relevance
“…In our study, small bowel ischemia was found in 42 patients (80.08%), colonic ischemia was found in 2 patients (3.8%) and both small bowel and colonic affection were present in 8 patients (15.4%), which match the results of Yusuf et al, 2016 where (72.4%) patients exhibited only small bowel involvement, but (27.6%) exhibited both small intestinal and colonic involvement [5].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, small bowel ischemia was found in 42 patients (80.08%), colonic ischemia was found in 2 patients (3.8%) and both small bowel and colonic affection were present in 8 patients (15.4%), which match the results of Yusuf et al, 2016 where (72.4%) patients exhibited only small bowel involvement, but (27.6%) exhibited both small intestinal and colonic involvement [5].…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the need for a new diagnostic marker is essential as earlier diagnosis with a simple laboratory test would be a major breakthrough. An ideal biochemical marker for AMI should be specific, sensitive, released from the intestinal mucosa to detect ischemia at the earliest stage, noninvasive and measurable in the peripheral blood [5].…”
Section: Introductionmentioning
confidence: 99%
“…These variables, other than NLR, have been already reported to be candidate predictors of bowel ischemia in patients with HPVG [16,[22][23][24][25][26][27]. However, no previous reports have described an association between high NLR and bowel ischemia in HPVG patients, although some researchers have suggested that NLR might be useful for the identi cation of, and assessment of the severity of, acute mesenteric ischemia [28]. Therefore, further research regarding the predictive value of NLR in larger groups of patients should be conducted, because some institutions do not routinely measure other variables, such as CRP [29].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, popular inflammatory markers such as mean platelet volume (MPV), red blood cell distribution width (RDW) and neutrophil / lymphocyte ratio have been studied 5 . MPV and RDW markers have been studied in the literature in many diseases ranging from acute appendicitis to mesenteric ischemia, from coronary artery disease to pulmonary embolism and have been accepted as important markers [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%